2009
DOI: 10.1002/cbdv.200800196
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Amino‐Acid Bridge on Binding Affinity and Cleavage Efficiency of Pyrenyl‐Macrocyclic Polyamine Conjugates toward DNA

Abstract: A series of pyrenyl-macrocyclic polyamines 5a-5c have been prepared and characterized. Their DNA-cleavage properties were examined under physiological conditions. Without the presence of other additives, the DNA cleavage ability of 5a-5c showed the order of 5c>5a>5b. Absorption and fluorescence experiments showed the binding affinity of 5a-5c to DNA. The interactions of 5a-5c with CT-DNA indicated that the DNA binding ability followed an order according to their cleavage efficiency. All the results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Steward et al demonstrated a four-arm, lattice-bearing, single-stranded DNA bound to the central Ni(II)-cyclen complex, which improves self-assembly at the supramolecular level, but its effect on duplexes is also unknown [4]. On the other hand, it is known that macrocyclic polyamines such as 1,4,7,10tetraazacyclododecane (cyclen) are potential artificial nucleases, and their derivatives can cleave double-stranded DNA (dsDNA), even without metal ions, through hydrolysis or oxidative cleavage [5][6][7][8][9]. Thus, covalent attachment of a macrocyclic amine to ssDNA may provide new and useful models for studying the function and in vitro use of artificial nucleic acid-based nucleases.…”
Section: Introductionmentioning
confidence: 99%
“…Steward et al demonstrated a four-arm, lattice-bearing, single-stranded DNA bound to the central Ni(II)-cyclen complex, which improves self-assembly at the supramolecular level, but its effect on duplexes is also unknown [4]. On the other hand, it is known that macrocyclic polyamines such as 1,4,7,10tetraazacyclododecane (cyclen) are potential artificial nucleases, and their derivatives can cleave double-stranded DNA (dsDNA), even without metal ions, through hydrolysis or oxidative cleavage [5][6][7][8][9]. Thus, covalent attachment of a macrocyclic amine to ssDNA may provide new and useful models for studying the function and in vitro use of artificial nucleic acid-based nucleases.…”
Section: Introductionmentioning
confidence: 99%